2004
DOI: 10.1097/01.tp.0000131170.67671.75
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Matrix Metalloproteinases MMP-2 and MMP-9 After Human Liver Transplantation: Increased Serum MMP-9 Level in Acute Rejection

Abstract: Patients with acute allograft rejection have elevated serum levels of MMP-9 1 week after OLT, which was most likely derived from inflammatory cells. An increased MMP-2 serum level and liver tissue content was found in patients with cirrhosis, which decreased after OLT. These observations indicate active involvement of MMP-2 and -9 in end-stage liver disease and OLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 27 publications
2
30
0
1
Order By: Relevance
“…(1), but occurred independent of the genotype. Serum levels of MMP-9 peak at 1 week after OLT, which is associated with acute allograft Statistical significance X = 9.9; P = 0.002 rejection, as previously reported [14]. Irrespective of a genotype mismatch between the donor and the recipient, we found a comparable serum MMP-9 peak and pattern over time (Fig.…”
Section: The Role Of Mmp Polymorphisms In Liver Transplantationsupporting
confidence: 85%
See 2 more Smart Citations
“…(1), but occurred independent of the genotype. Serum levels of MMP-9 peak at 1 week after OLT, which is associated with acute allograft Statistical significance X = 9.9; P = 0.002 rejection, as previously reported [14]. Irrespective of a genotype mismatch between the donor and the recipient, we found a comparable serum MMP-9 peak and pattern over time (Fig.…”
Section: The Role Of Mmp Polymorphisms In Liver Transplantationsupporting
confidence: 85%
“…The extracellular matrix may also be an important target in the process of acute rejection after orthotopic liver transplantation (OLT). In a previous study we demonstrated elevated serum levels of MMP-9 at 1 week after OLT in patients with acute allograft rejection [14].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…We also looked for any expression differences in extracellular matrix proteins in AR, because some of these have been previously demonstrated to be differentially expressed in AR. 15 We observed that whereas UMOD gene expression in AR biopsy was significantly lower in AR [false discovery rate (FDR) ϭ 0.02%; similar results to the low UMOD peptide abundance in AR urine], the three collagen genes (COL1A2, FDR ϭ 0.18%; COL3A1, FDR ϭ 0.67%; COL4A1, FDR ϭ 1.82%) were upregulated in AR (different from low collagen peptide abundance in AR urine). Gene expression for matrix metalloproteinase-7 (MMP-7; FDR ϭ 0.03%), tissue inhibitor of metalloproteinase 1 (TIMP1; FDR ϭ 24%), and the serpin peptidase inhibitor (SERPING1; FDR ϭ 33%) was higher in AR when compared with STA biopsies, although only MMP7 expression was significant.…”
Section: Integrated Analysis Of Matched Samples: Transcriptional Analmentioning
confidence: 51%
“…In addition, MMP-9 (gelatinase B), a member of MMPs, is derived mainly from Kupffer cells in the liver, 38 and its expression is significantly increased together with the activation of cells, indicating that MMP-9 could be a marker of Kupffer cell activation instead of its activity as a collagenase. A number of studies have shown increased serum and plasma levels of MMP-9 in various types Pathophysiology of steatohepatitis Y-p Mu et al of liver injury, including ischemic reperfusion injury 39 and chronic viral hepatitis. 40,41 Furthermore, the mutation of MMP-9 was reported to inhibit hepatic fibrogenesis in mice.…”
Section: Discussionmentioning
confidence: 99%